La poética del cómico en Arrested Development y la revisibilidad (2012)
The article analyzes the construction processes of comedy in the Americansitcom Arrested Development. Considered by specialized critics as anexample of innovation in language and semiotic density, the program is anexample of the kind of textual construction that is inserted into the phenomenonof the American reversibility proposed by North American JasonMittel. When analyzing poetic processes in the construction of anagrammatichumor and multi-isotope, we explain the demand that the text thatgenerates for repeated reading processes that may deplete their mevanings.